Foreign Direct Investments: A study based on the Indian Economy. - Kapoor, Vikas (2007)
Over the past few years, India's inward Foreign Direct investment (FDI) has attracted many scholars interest. The objective of this study is to focus on the impact that Foreign Direct investment has for Indian economic growth and development. It seeks to briefly reveal why there has been a recent surge in FDI and also the factors from attracting foreign direct investments. Main determinants of FDI will also be revealed in this paper. In addition, this paper also compares the performance of china and India in terms of attracting FDI. This study also reveals importance of India's liberalization policies in attracting FDI. Thus it becomes necessary to study impact of such inflows as it has important policy implications.